COVID-19 Vaccine Booster: To Boost or Not to Boost - Rahul Shekhar; Ishan Garg; Suman Pal; Saket Kottewar; Abu Baker Sheikh (MDPI AG, 2021)
Developing safe and effective vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) at a breakneck speed has been an exceptional human achievement. It remains our best hope of containing the coronavirus disease 2019 (COVID-19) pandemic. However, newer, more aggressive SARS-CoV-2 viral strains, as well as the possibility of fading immunity following vaccination, have prompted health officials to investigate the necessity for additional immunization. This has put further pressure on disregarded human life in lower-income countries that already have minimal access to COVID-19 vaccines. The Centers for Disease Control and Prevention (CDC) have recommended a third COVID-19 vaccine dose in immunocompromised individuals in a recent announcement. Governments and health care officials need to develop usage guidelines for COVID-19 vaccine booster doses while considering the dangers of potential waning immunity and new viral strains and prioritizing vulnerable populations everywhere, including those living in lower-income countries.